Intergroup communication in online communities: an analysis of americanwx.com. - Koehle, Joseph E. Jr (Kansas State University, 2011)
Social Identity Theory has long held that group affiliation plays a predominant role in how we interact with others and the types of communication strategies that we deploy. Traditional scholarship on Computer Mediated Communication maintains an excessively interpersonal focus, detracting from its ability to theorize intergroup communication and conflict. This research study, conducted at the Internet bulletin board Americanwx.com, investigates the role that group identity plays in the everyday discourse of online message boards. In an ethnographic study spanning the course of 8 months and thousands of exchanges, research found that the structure of message boards themselves is implicated in the formation and maintenance of groups, and that once formed, groups tend to act in a manner that is consistent with Social Identity Theory.
Keywords: Virtual communities; Intergroup communication; Computer mediated communication; Communication (0459)